2018
DOI: 10.3389/fimmu.2018.01798
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Antimyeloma Activity of Dendritic Cells and Pomalidomide in a Murine Myeloma Model

Abstract: We have previously shown that immunization with tumor antigen-loaded dendritic cells (DCs) and the immunomodulating drug, lenalidomide, synergistically potentiates the enhancing antitumor immunity in a myeloma mouse model. In this study, we investigated the immunogenicity of DCs combined with pomalidomide and dexamethasone in a myeloma mouse model. MOPC-315 cells were injected subcutaneously to establish myeloma-bearing mice. Four test groups were used to mimic clinical protocol: (1) PBS control, (2) DCs, (3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…The immunological mechanism of iMiDs involves the down-regulation of regulatory T-cells (Tregs) and myeloid-derived suppressor cells (MDSCs) in the tumor microenvironment and an enhancement of the immune response by activating NK cells and T-cells [29]. We previously reported a strong synergistic effect of DC vaccination and lenalidomide [30] or pomalidomide [31] in the induction of an anti-myeloma effect in a murine myeloma model. Another method to improve DC vaccination is to combine checkpoint blockades that modulate negative regulation in the tumor microenvironment [32].…”
Section: Dendritic Cell Vaccinationmentioning
confidence: 99%
“…The immunological mechanism of iMiDs involves the down-regulation of regulatory T-cells (Tregs) and myeloid-derived suppressor cells (MDSCs) in the tumor microenvironment and an enhancement of the immune response by activating NK cells and T-cells [29]. We previously reported a strong synergistic effect of DC vaccination and lenalidomide [30] or pomalidomide [31] in the induction of an anti-myeloma effect in a murine myeloma model. Another method to improve DC vaccination is to combine checkpoint blockades that modulate negative regulation in the tumor microenvironment [32].…”
Section: Dendritic Cell Vaccinationmentioning
confidence: 99%
“…In support of our findings, the addition of DEX to the DC vaccination plus IMiDs does not have a negative antimyeloma effect compared with the combination without DEX in a model of murine MM. 20 This is the first report of a potential mechanism whereby IMiD treatment leads to the onset of itchy skin with rash-like atopy. Understanding LEN-related rashes provides valuable insight into the response to LEN treatment and may enable improved treatment regimens for MM.…”
Section: Discussionmentioning
confidence: 82%
“…There is evidence of immunomodulatory activity of IMiDs on mouse dendritic cells (DCs) 13,17 and a synergistic effect with DC vaccination in model of murine MM [18][19][20] or colon cancer, 21 however, only a few reports have examined its effects on human DC subsets. [22][23][24][25] DCs are capable of inducing Th1 or Th2 responses.…”
Section: Introductionmentioning
confidence: 99%
“…In order to increase the efficiency some investigators have attempted a combination of DC vaccine with the drug Lenalidomide for treatment of MM (29) and colon cancer (30) in murine model. In yet another study pomalidomide and dexamethasone were combined with DC vaccine and tested in murine MM model (31). Vo et al (32) have also shown that addition of Lenalidomide in different concentrations in vitro on Mo-DCs obtained from multiple myeloma patients improved the functionality of DC.…”
Section: Discussionmentioning
confidence: 99%